2012
DOI: 10.5533/1984-2503-20124303
|View full text |Cite
|
Sign up to set email alerts
|

El Derecho a La Vivienda Adecuada en Las Normas Legales De Argentina, Paraguay Y Uruguay (1990-2010)

Abstract: RESUMENEste trabajo busca contribuir con los debates actuales sobre la definición y los alcances del derecho a la vivienda adecuada, mediante la descripción, interpretación y análisis comparativo de la forma en que éste ha evolucionado en las normas legales de Argentina, Paraguay y Uruguay en el período 1990-2010 2 . El análisis propuesto se apoya en herramientas conceptuales provenientes del derecho internacional de los derechos humanos. Conocer de qué forma se ha configurado normativamente este derecho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the other hand, in Figure 2 b, it is observed that the countries in Latin America that have mainly been researched in terms of accessibility in housing are Brazil at 61%, followed by Chile at 16%, Colombia at 9%, Ecuador at 5%, and then Mexico and Argentina with 4%. Finally, mixed classification represents only 1% of the studies, with three countries—Argentina, Paraguay, and Uruguay—analysed and compared in terms of the regulations on accessibility in those countries [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, in Figure 2 b, it is observed that the countries in Latin America that have mainly been researched in terms of accessibility in housing are Brazil at 61%, followed by Chile at 16%, Colombia at 9%, Ecuador at 5%, and then Mexico and Argentina with 4%. Finally, mixed classification represents only 1% of the studies, with three countries—Argentina, Paraguay, and Uruguay—analysed and compared in terms of the regulations on accessibility in those countries [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the distribution by type of accessibility (first graph, Figure 3 ), the so-called “general” group predominates with 46%, in which no specific disability is analysed, but mainly regulatory issues for disabled people ( n = 5) [ 49 , 54 , 64 , 82 , 93 ] or housing improvements for disabled people ( n = 20) [ 44 , 45 , 48 , 53 , 55 , 58 , 65 , 67 , 68 , 73 , 76 , 80 , 84 , 85 , 86 , 90 , 91 , 96 , 97 , 98 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations